(untitled) (Fiep Bulletin - online, 2013)
This is a descriptive study of the integrative literature review type. The survey was conducted in LILACS database, books and online information, taking as a keyword Shantala. The survey objectived to identify in literature the Shantala massages technique. As a result, was identified that the Shantala technique had its origin in southern India, in the region called Kerala. In the 70, the Shantala massage was brought west by French obstetrician Frédérick Leboyer, after observing in Calcutta, India, a mother massaging her baby. The technique should be done with the naked baby in a heated place, using natural oils and the mother must be seated on the floor, with stretched legs, upright back and relaxed shoulders to perform the massage with her hands in baby’s chest, arms, hands, belly, legs, back, face and, finally, during the bath. All these massages are intended to facilitate the expansion of breathing, balance and harmony to the baby; releasing tensions in cervical and dorsal regions; stimulating motor coordination; facilitate the intestines function and gases elimination, and brings relief from cramps; strengthens the muscles and joints; activates movement, stimulates the nervous system, relieve the tension of the vertebrae, giving comfort and relaxation to the baby, preparing it to crawl and walk. No massage can be performed before the baby have a month, do not touch the belly while the child does not have a month and, in the same way, it is important to wait a month to touch the face. The massage can be made at least in the first four months. Once the child can already be turning, get a straight position, and, thus, distend the back and spine, the massage should be suspended.